RELATIONSHIP BETWEEN OF PERCEPTION OF PERSONALITY DEVELOPMENT PROGRAM WITH SELF-CONTROL FOR PRISONER IN WOMEN PRISON CLASS IIA SEMARANG - Ervina Safitri; Kartika Sari Dewi (Jurnal EMPATI, 2013)
Increasing of women criminality levels in Indonesia one of them is because low self-control. Self-control is influenced by socialization, cognitive, and emotional adjustment factors. Socialization factors create cultivation of good values for prisoner through the perception of personality development. This study aimed to know the relationship between perceptions of personality development program with self-control for prisoner in Women prison Class IIA Semarang.Population in this research is 236 prisoner with 142 prisoner sample. Random sampling technique is used in this research. Participant were ask to complete 28 item of non verbal aggresivity scale (α=0.925) and 45 item perception of mental improvement scale (α=0.934). Data collection using the Scale Perceptions of Personality Development Program consists of 33 aitem (α = 0.928) and the Self-Control Scale consists of 24 aitem (α = 0.893).Simple regression analysis results indicate a positive and significant relationship between perceptions of personality development program with self-control for prisoner shown by the number of correlation r xy = 0.604 and p = 0.000 (p <0.05) so that the hypothesis that there is a positive relationship between perceptions the personality development program with self-control is acceptable. Relationship between the two variables is if the perception of personality development program is more positive, then the level of self-control is also higher. Otherwise, if the perceptions of personality development program is more negative, than the self-control is also lower.